Can Peripartum Plasma Profiles of Steroid Hormones, Metabolites and Minerals Predict Postpartum Fertility in Buffaloes? - Kalasariya, R.M.; Dhami , A.J.; Parmar , S.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The plasma profile of various hormonal, biochemical and mineral constituents was studied in 32 buffaloes under nutritional management of transition period for 2 months before to 2 months postpartum. The buffaloes that expressed estrus and conceived within 120 days postpartum, irrespective of nutrient treatment or control groups, were classified as fertile (n=15) and rests as infertile (n=17) buffaloes. The variations in blood glucose and plasma profile of progesterone, estradiol, protein, cholesterol, triglycerides, Ca, P, Mg and trace minerals (Zn, Fe, Cu, Co, Mn), if any, on day 60, 30, 15 prepartum, on the day of calving, and on day 15, 30, 45 and 60 postpartum in postpartum conceiving and non-conceiving buffaloes were examined. There was no significant effect of fertile-infertile groups on plasma P4 and E2 profile on any day, except on day 45 postpartum, where E2 was (p
Keywords: Buffalo; Postpartum; Fertile; Infertile; Metabolic profile; Steroid hormone profile